A study of staff pre-evacuation behaviors in a Malaysian hotel - Noumeur A; Lovreglio R; Md Said MS; Baharudin MR; Yusoff HM; Mohd Tohir MZ (John Wiley and Sons, Ltd., 2024)
Simulating fire and evacuation scenarios is crucial for engineers to assess building safety during fire incidents. Accurate simulations require data on occupants' behaviors, particularly during the pre-evacuation phase as these decisions significantly impact evacuation duration. Gathering comprehensive data from diverse regions while considering cultural and regional variations is necessary to understand how occupants' behavior is influenced. Thus, this study focuses on examining the behavior of Malaysian hotel staff during unannounced fire drill to gain insights into factors affecting their behavior during pre-evacuation stage, such as fire experience, fire alarm, drill participation, fire training, and awareness. The study categorizes the actions performed by the hotel staff into sequences and analyses them based on influencing factors. The findings indicate that instead of immediately evacuating in response to emergency notification, the hotel staff engage in various actions. Most staff members initially investigate or ignore the emergency, resulting in longer pre-evacuation times. Moreover, the results suggest that previous drill participation and high awareness levels contribute to shorter pre-evacuation times. Conversely, previous fire experience, fire training, and fire alarm familiarity have no effect on pre-evacuation time.
Keywords: building evacuation; evacuation drill; human behavior; influencing factors